The Role of Governance Mechanisms in Banks to Promote Informational Disclosure: An exploratory research in a sample of Iraqi - وجدان فالح حسن; جنان مهدي (Iraqi Journal for Administrative Sciences, 2024)
The aim of this research is to identify the impact of applying governance through its mechanisms, and the role that these mechanisms play to ensure the achievement of the dimensions of information disclosure to improve the financial statements that include financial reports that reflect negatively or positively on the efficiency of financial markets. In order to prove the hypothesis of the research, the researcher adopted the descriptive analytical approach and the questionnaire, and a questionnaire was designed for the analysis on the research sample represented by (7) from Iraqi banks, and the research community consisted of employees in banks where (150) questionnaires were distributed among them (118) and represented (78.7%). . Statistical programs (spss) were used to analyze the questionnaire data. The research reached the most important conclusions: the necessity of applying governance mechanisms to enhance the efficiency of banks' performance and to help managers and the board of directors follow a correct policy to ensure investors' money and increase their confidence in Iraqi banks. As for the recommendations: the need for Iraqi banks to use the modern technology strategy as a means to enhance the dimensions of disclosure by disseminating information to serve the needs of users of financial reports, leading to achieving their confidence and full satisfaction, which provides them with the motivation to deal with the bank.